ENERGY CONSUMPTION AND WEAR RATE OF DIAMOND BEADS DURING OPERATION OF A DIAMOND WIRE SAW - Tomislav Korman; Trpimir Kujundžić; Šime Vrandečić (e-Zbornik. Elektronički Zbornik Radova Građevinskog Fakulteta, 2023)
Diamond wire saws are indispensable machines for the extraction and processing of dimension stones. The cutting speed, energy consumption and wear rate of the diamond beads are the most important factors in assessing the efficiency of a diamond wire saw. The parameters that influence the efficiency of the diamond wire saw can be divided into controlled and uncontrolled parameters. Uncontrolled parameters cannot be influenced directly and are related to the rock types and their properties such as strength, hardness and abrasiveness. Controlled parameters are related to the operating parameters and technical characteristics of the machine. The energy consumption and the service life of the diamond wire are directly related to the characteristics of the machine and the design of the diamond wire, such as the power of the drive motor, the diameter of the drive wheel, diamond grit size and the diameter of the wire. The operating parameters of the diamond wire saw, such as cutting speed, cutting surface, cutting angle, wire tension and cooling water flow, also have a significant influence. Based on previous studies, the influence of the above parameters on the consumption of energy and wear rate of diamond beads in the operation of a diamond wire saw was analyzed.